Bayesian vs. frequentist inference - an ophtalmic study on ocular perfusion pressure - Tojtovska Ribarski, Biljana; Ribarski, Panche; Ljubic, Antonela; Dimitrova, Galina (My University, 2024)
This study investigates the application of Bayesian statistical methods for comparing ocular perfusion pressure (OPP) between glaucoma and non-glaucoma populations, contrasting it with traditional frequentist approaches. Using OPP measurements from two patient groups, we employ partially informed Bayesian models to test the hypothesis of no difference in means between the groups. We calculate Bayes factor using Savage-Dickey density ratio and offer insights in the hypothesis beyond p-values. The results highlight the advantages of the Bayesian approach, including its flexibility in incorporating prior information and interpreting evidence. We discuss the limitations and potential biases introduced by the choice of priors. This paper contributes to the understanding of Bayesian inference in ophthalmic research and emphasizes its potential for hypothesis testing in clinical studies.
Keywords: OCULAR PERFUSION PRESSURE; BAYESIAN INFERENCE; FREQUENTIST STATISTICS; BAYES FACTOR; R; JAGS